Salvage Surgery Rates for Pediatric Testicular Torsion: Comparison of the Pre- and Post-Quality Metric Eras. Issue 2 (28th August 2022) - Chun, Brian; Colaco, Marc; Fox, Janelle A.; Cannon, Glenn M.; Schneck, Francis X.; Chaudhry, Rajeev; Villanueva, Jeffrey
Abstract : Purpose: Pediatric testicular torsion is a urological emergency that requires timely intervention. In 2015, quality metrics for testicular torsion were implemented in the U.S. News & World Report "Best Children's Hospitals" rankings. Our study examines and compares testicular salvage surgery rates before and after the institution of national quality metrics from a multi-institutional database. Materials and Methods: The Pediatric Health Information System® was surveyed for all testicular torsion encounters using ICD (International Classification of Diseases), Ninth and Tenth Revisions coding from 52 hospitals between January 2010 and December 2019. Patients <1 year and ≥18 years of age were excluded. Only hospitals that reported outcomes before and after quality scoring were included. Testicular salvage surgery was defined as patients having undergone orchiopexy without concomitant orchiectomy. Age, race, distance from hospital, household income and insurance status were compared. Results: A total of 890 patients (551 pre-metric and 339 post-metric) from 38 hospitals were included. The testicular salvage surgery rate was 12.5% higher in the post-metric cohort (70.9% versus 58.4%). Hospital compliance to testicular torsion quality metrics increased from 62% in 2015 to 98% in 2019. Mean age, race, distance to hospital, household income, insurance status and use of ultrasound were not statistically different between pre- and post-metric cohorts. Conclusions: Since the implementation of quality metrics, salvage surgery rates for testicular torsion increased to 70.9%, an improvement of 12.5% when compared to pre-metric outcomes. Patient factors were similar between the 2 groups. Multi-institutional prospective data are needed to validate this database study and evaluate overall testicular salvage rate.